2020
DOI: 10.21203/rs.3.rs-52276/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic selection for growth drives differences in intestinal microbiota composition and parasite disease resistance in gilthead sea bream

Abstract: Background: The key effects of intestinal microbiota in animal health has led to an increasing interest in manipulating these bacterial populations to improve animal welfare. The aquaculture sector is no exception and in the last years many studies have described these populations in different fish species. However, this is not an easy task, as intestinal microbiota is composed of very dynamic populations that are influenced by different factors, such as diet, environment, host age and genetics. In the current… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 62 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…There is a limited number of studies defining the effects of the host genome on intestinal microbiota composition in fish, but it has been demonstrated that there is a clear correlation between fish genotype and intestinal microbial communities. As reported by Piazzon et al (2017, 2020), the genetic background influences the structure of the commensal bacterial communities and their fluctuations upon differences in diet. Moreover, the authors showed that the genetic background, microbiota composition, and dietary and physiological plasticity are intricately linked (Piazzon et al, 2020).…”
Section: Genetic Effectsmentioning
confidence: 76%
See 2 more Smart Citations
“…There is a limited number of studies defining the effects of the host genome on intestinal microbiota composition in fish, but it has been demonstrated that there is a clear correlation between fish genotype and intestinal microbial communities. As reported by Piazzon et al (2017, 2020), the genetic background influences the structure of the commensal bacterial communities and their fluctuations upon differences in diet. Moreover, the authors showed that the genetic background, microbiota composition, and dietary and physiological plasticity are intricately linked (Piazzon et al, 2020).…”
Section: Genetic Effectsmentioning
confidence: 76%
“…As reported by Piazzon et al (2017, 2020), the genetic background influences the structure of the commensal bacterial communities and their fluctuations upon differences in diet. Moreover, the authors showed that the genetic background, microbiota composition, and dietary and physiological plasticity are intricately linked (Piazzon et al, 2020). Results obtained in this trial suggest that genetic background of GSB influences the structure of the commensal bacterial communities and that the typical microbial architecture of the anterior intestine of the three different groups of families of GSB selected by growth fed two different diets do not differ significantly in their overall core composition.…”
Section: Genetic Effectsmentioning
confidence: 76%
See 1 more Smart Citation